Computed Tomography Images Based Measurement of Caudate to Right Lobe Ratio of Liver in Adult Population in a Tertiary Care Hospital - Sah, Ramswarth; Mandal, Brajesh Kumar; Khanal, Umesh Prasad; Pradhan, Bijay Lal; Joshi, Ram Datt; Gurung, Ghanshyam; Pradip Kumar Chapagain (Journal of College of Medical Sciences-Nepal, 2025)
Background Liver volume changes in cases of liver cirrhosis due to enlargement in caudate lobe and shrinkage in the right lobe. The caudate-to-right lobe ratio is essential for assessing liver volume redistribution. The caudate-to-right lobe ratio value <0.6 is normal, between 0.6 and 0.65 is borderline, >0.65 suggests cirrhosis and over 0.73 is cirrhotic in 99% cases. Aim of this study was to analyze the morphometric measurement of the liver and calculate caudate-to-right lobe ratio in the Nepalese population using contrast-enhanced computed tomography and compare the values with previously documented studies to provide baseline data. Methods This analytical cross-sectional study was performed from September 2023 to September 2024 after ethical clearance (Ref. No.: 296/080/081(6-11) E2). Data (measurement of the transverse diameter of the caudate and right lobe) of all patients undergoing contrast-enhanced computed tomography examination of the abdomen without any liver pathology necessitating the examination during the study period. The caudate-to-right lobe ratio was calculated from the measurement. Data were analyzed using the SPSS (version 16). Results Among the 200 cases, 88 (44.00%) were male and 112 (56.00%) were female. We found 46 years (IQR: 25-75) as median age of the participants. The mean liver span, transverse diameter of the caudate lobe, right lobe, and caudate-to-right lobe ratio were 12.34±1.24 cm, 3.71±0.60 cm and 8.40±0.80 cm and 0.45±0.08 respectively. Conclusions The caudate-to-right lobe ratio was found 0.45±0.08 in normal adult study population. The caudate-to-right lobe ratio was found not correlated with age or sex.